Transcriptomic response of Trematomus bernacchii to short- to medium-term mild heat stress and experimental design bias - S. Greco; A. S. Gaetano; A. Pallavicini; P. G. Giulianini; M. Gerdol (SIICS, 2022)
Many stenotherm marine species live in the cold and stable environment of the Antarctic Ocean which could be impacted by climate change in the upcoming years. To investigate how antarctic fish would cope with this issue, gene expression analysis was carried out on Trematomus bernacchii specimens caught near Mario Zucchelli Station. Brain, gill and muscle tissues were sampled from naïve (right after catch) animals and from those kept in control (-0.9°C) and experimental (+0.6°C) tanks for six hours, seven and twenty days post acclimation. RNAseq data showed that the temperature increase mostly affected the brain, which showed a time dependent response. Immune response was up-regulated at seven days of exposure; protein turnover and energy management were down-regulated and and neuronal remodeling related genes were up-regulated at 20 days, where the highest number of differentially expressed genes was observed. Gill tissue showed a mild response after 20 days, mostly involving DNA replication. A notable early-starting response to stabling was also observed across the entire experiment in brain and gills, with the latter being the most affected. Expression pattern clustering analysis was performed, showing that many synapse-related genes were down-regulated and energy-related genes were up-regulated, while several binding processes were up-regulated at the latest time point in the brain. The Response in gills was milder and mostly involved cytoskeleton and glycolysis related genes. No significant change was observed in muscle. These results show that the brain is the tissue most affected by heat and confinement, demonstrating how sensitive it's to the smallest environmental changes and the importance of careful experimental design when working with captive wild organisms.